State-Dependent Propagation of Neuronal Sub-Population in Spontaneous Synchronized Bursts - Yada, Yuichiro; Kanzaki, Ryohei; Takahashi, Hirokazu (Frontiers in Systems Neuroscience, 2016)
Repeating stable spatiotemporal patterns emerge in synchronized spontaneous activity in neuronal networks. The repertoire of such patterns can serve as memory, or a reservoir of information, in a neuronal network; moreover, the variety of patterns may represent the network memory capacity. However, a neuronal substrate for producing a repertoire of patterns in synchronization remains elusive. We herein hypothesize that state-dependent propagation of a neuronal sub-population is the key mechanism. By combining high-resolution measurement with a 4,096-channel complementary metal-oxide semiconductor microelectrode array and dimensionality reduction with non-negative matrix factorization, we investigated synchronized bursts of dissociated rat cortical neurons at approximately three weeks in vitro. We found that bursts had a repertoire of repeating spatiotemporal patterns, and different patterns shared a partially similar sequence of sub-population, supporting the idea of sequential structure of neuronal sub-populations during synchronized activity. We additionally found that similar spatiotemporal patterns tended to appear successively and periodically, suggesting a state-dependent fluctuation of propagation, which has been overlooked in existing literature. Thus, such a state-dependent property within the sequential sub-population structure is a plausible neural substrate for performing a repertoire of stable patterns during synchronized activity.